Dying of cancer in Italy: impact on family and caregiver. The Italian Survey of Dying of Cancer. Issue 6 (11th May 2007) - Rossi, Paolo Giorgi; Beccaro, Monica; Miccinesi, Guido; Borgia, Piero; Costantini, Massimo; Chini, Francesco; Baiocchi, Diego; De Giacomi, Giovanna; Grimaldi, Maria; Montella, Maurizio
Abstract : Objective: To describe the effect of terminal cancer on the patient's family, finances and daily life. Methods: A cluster sample of 2000 adults (⩾18 years old) who had died from cancer, and who were representative of Italy, was studied. 1900 caregivers were identified and 68% responded to a post-bereavement survey. Caregivers included the patient's child (46%), his/her spouse (31%), other relatives or friends (20%) or a health professional (3%). The median age of a caregiver was 54 years and 69% were females. During the last 3 months of the patient's life, 44% of caregivers reported difficulties in their regular employment. Results: Of the 68% of families who had to pay for some of the care, 37% had to pay for drugs, 36% for nursing and assistance and 22% for physicians. Paying for care was more frequent in the south of Italy (OR 2.5; 95% CI 1.0 to 6.3) and when the patient was a housewife (OR for unit increase 2.7; 95% CI 1.6 to 6.1). To cover the costs of patient care, 26% of families used all or most of their savings. Economic difficulties were greater in the south of Italy (OR 3; 95% CI 1.8 to 5.1), for female caregivers (OR 1.4; 95% CI 1.0 to 1.9) and for disadvantaged patients. The duration of time the patient was completely dependent strongly determined the effect caregiving had on their regular employment and on the family's financial situation. Conclusions: Although in Italy families are responsible for a small percentage of the overall costs of patient care, the effect of cancer on savings and daily life can be substantial. Strong geographical and gender differences emerged from this study.